Effect of increased wood harvesting and utilization on required greenhouse gas displacement factors of wood-based products and fuels. (1st October 2019) - Seppälä, Jyri; Heinonen, Tero; Pukkala, Timo; Kilpeläinen, Antti; Mattila, Tuomas; Myllyviita, Tanja; Asikainen, Antti; Peltola, Heli
Abstract: A displacement factor ( DF ) may be used to describe the efficiency of using wood-based products or fuels instead of fossil-based ones to reduce net greenhouse gas (GHG) emissions. However, the DFs of individual products and their production volumes could not be used alone to evaluate the climate impacts of forest utilization. For this reason, in this study we have developed a methodology to assess a required displacement factor ( RDF ) for all wood products and bioenergy manufactured and harvested in a certain country in order to achieve zero CO2 equivalent emissions from increased forest utilization over time in comparison with a selected baseline harvesting scenario. Input data for calculations were produced with the simulation model, Monsu, capable of predicting the carbon stocks of forests and wood-based products. We tested the calculations in Finnish conditions in a 100-year time horizon and estimated the current average DF of manufactured wood-based products and fuels in Finland for the interpretation of RDF results. The results showed that if domestic wood harvesting will be increased by 17–33% compared to the basic scenario, the RDF will be 2.0 to 2.4 tC tC −1 for increased wood use in 2017–2116. However, the estimated average DF of manufactured wood-based products and fuels currently in Finland was less than 1.1 tC tC −1 . The results indicate strongly that the increased harvesting intensity from the current situation would represent a challenge for the Finnish forest-based bioeconomy from the viewpoint of climate change mitigation. For this reason, there is an immediate need to improve reliability and applicability of the RDF approach by repeating corresponding calculations in different circumstances and by improving estimations of DF s on country levels. Highlights: Displacement factor (DF) describes the substitution climate impact of wood use. We estimated required displacement factor (RDF) to achieve zero emissions. RDF should be 2.0–2.4 tC tC −1 for increased wood use in 2017–2116 in Finland. RDF appears greater than the estimated current average DF . This is a threat for forest-based bioeconomy from the climate change viewpoint.